PENERAPAN KONSELING RATIONAL EMOTIVE BEHAVIORAL DALAM MENGURANGI TINGKAT IRRATIONAL BELIEF KAUM LESBIAN - Silvianetri Silvianetri (IAIN Batusangkar, 2018)
Most lesbians are irrational belief in the opposite sex. They consider men to be untrustworthy and evil people. This can be obtained from a bad experience in the family, in which the father is less pleasant towards the mother and from a hostile environment. This condition fosters irrational belief of lesbians towards men. Based on these facts, this study aims to reveal how the application of rational emotive behavioral counseling in reducing the level of irrational belief of lesbians. The research method used is action research. The treatment consists of two cycles, in which one cycle consists of four stages, namely (1) planning, (2) implementation, (3) observation, (4) reflection. Especially at the implementation stage of the counseling steps used are; (a). Accessing the client's self talk, (b). Determining the client's underlying belief, (c) Agreeing on more rational belief, (d) Performing rational emotive imagery, (e). Assigning homework, (f) Positive consequence, and (g) Negative consequence. Respondents in this study amounted to 3 people who indicated lesbians. Respondents were taken based on descriptive random sampling. The results of the analysis of research data revealed that rational emotive behavioral counseling can reduce the level of irrational belief of lesbians. Based on these empirical data it can be concluded that counselors can use rational emotive behavioral counseling in reducing the level of irrational belief of lesbians, so that it is expected to reduce lesbian behavior in society.